Researching belonging with people with learning disabilities: Self‐building active community lives in the context of personalisation. (11th June 2021) - Kaley, Alexandra; Donnelly, John Paul; Donnelly, Lisa; Humphrey, Sally; Reilly, Steven; Macpherson, Hannah; Hall, Ed; Power, Andy
Accessible Summary: We wanted to understand more about how people with learning disabilities are building active community lives to help belonging. We spoke to 39 people from 29 different support organisations, 7 local authority representatives and 43 people with learning disabilities. They said belonging was about having the time to connect with other people in "everyday" places, being part of a supportive network and having the right choice and information. Belonging is like a cake. It needs the right ingredients. These ingredients include the right combination of people, places and times. Because of cuts to funding, many people with learning disabilities lack the right support, choice and information to access their communities. This is not belonging. Abstract: Background: This journal article draws on findings from a research project that examined how people with learning disabilities and their allies were seeking to build a sense of belonging. We wanted to focus on the concept of "belonging" in the context of personalisation and reduced government social care funding. Specifically, we sought to understand how people with learning disabilities and their supporters were coming together to "self‐build" networks of support including friendship clubs and self‐advocacy groups to enable a greater sense of belonging in their local communities. Methods: Qualitative interviews were conducted with seven local authority representatives across four case study areas in the UK, as well as 39 staff across 29 organisations providing a range of day and evening support and activities. We also talked to 43 people with learning disabilities across the four areas about their experiences. Findings: Our findings demonstrate how belonging involves a complex configuration of actors, places, times, relationships and institutional roles (much like the ingredients in a cake). The ways in which belonging intersects with agency and choice was also identified as an important and novel finding of our study. Conclusion: While belonging is often presented to people as a desirable and realisable outcome of social inclusion policies, cuts in funding and a lack of appropriate support frustrate people's desires to meaningfully belong with other people in their local community. This demonstrates the importance of supporting social environments that meet people's needs for social connectedness and belonging.